A rare case in childhood: Pott’s puffy tumor developing secondary to frontal sinus osteoma - Öztürk, Necmiye (Turk Pediatri Ars, 2020)
Pott’s puffy tumor is a rare and serious complication of frontal sinusitis, characterized by the development of osteomyelitis and subperiostal abscess in the frontal bone. Paranasal sinus osteomas are benign osteoblastic tumors, usually seen in the 3(rd) and 4(th) decades of life. In this report, we present a case of Pott’s puffy tumor due to frontal sinus osteoma in an adolescent male patient. In the literature, we found no similar case in the pediatric age group and we wanted to emphasize the development of Pott’s tumor as a rare complication of chronic or recurrent sinusitis and draw attention to the fact that paranasal sinus osteomas may be the underlying cause.